Introduction: (De)democratisation in Slovenia and Montenegro: Comparing the Quality of Democracy - Komar Olivera (Sciendo, 2020)
This paper creates a framework for the comparison of two similar and yet different democratisation cases – Slovenia and Montenegro. The two countries have obvious similarities: their geography and small population, as well as their common socialist Yugoslav heritage and common aspirations to join international organisations, most importantly the European Union. However, while Slovenia went through the democratisation process rather smoothly, Montenegro took the longer road, struggling for more than a decade to regain its independence and complete its transition. We take into account different internal and external factors in these two cases such as the year of independence and of joining NATO, the political and electoral system, ethnic homogeneity, the viability of civil society, EU integration status, economic development and the presence of war in each territory in order to identify and describe those factors that contributed to the success of democratisation in different areas: the party system, the interest groups system, the defence system, Europeanisation and social policy. We find that the democratisation process in these countries produced different results in terms of quality. Various objective measures of the quality of democracy score Slovenia higher compared to Montenegro, while public opinion data shows, in general, greater satisfaction with the political system and greater trust in political institutions in Montenegro than in Slovenia.